Communication and Teamwork Factors Affect the Performance of Amalia Medika Riau Hospital Nurses - Alisha, Nori; Efendy, Ismail; Fitriani, Arifah Devi (PROMOTOR, 2025)
The performance of inpatient nurses at AmaliaMedika Riau Hospital has not been implemented optimally, this is due to ineffective two-way communication both to superiors and fellow nurses. Teamwork that is not well established, so that there is work that is not carried out optimally. The purpose of this study is to determine the influence of communication and teamwork on the performance of nurses at Amalia Medika Riau Hospital. The research design used in this study is quantitative research. The population in this study is all nurses in the inpatient room at Amalia Medika Riau Hospital as many as 45 people. The sampling technique uses the saturated sample technique so that the sample totals 45 people. The data collection technique uses a questionnaire. Data analysis was carried out by univariate and bivariate analysis with chi square and multivariate tests. The results of the study showed that there was an influence of communication on the performance of nurses at Amalia Medika Riau Hospital and there was an influence of teamwork on the performance of nurses at Amalia Medika Riau Hospital. A multivariate analysis was obtained that the communication variable had the most influence on the performance of nurses at Amalia Medika Riau Hospital. The conclusion in this study is that there is an influence of communication and teamwork on the performance of nurses at Amalia Medika Riau Hospital and the variable that has a higher chance is communication. The implication of this study is that the performance of inpatients at Amalia Media Riau Hospital can be improved by improving two-way communication by creating openness, empathy and mutual support between fellow nurses and superiors. Improving the teamwork of inpatient nurses by contributing both energy and mind to improve performance.